Sistem Pendukung Keputusan Prioritas Pembangunan Di Desa Tekad Menggunakan Metode TOPSIS - Ariyansyah Ariyansyah; Bella Cahya Juwita; Muhamad Muslihudin (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2018)
Development priority is a series of government policies implemented through a national development planning process that has a significant impact on the economy both at the central and regional levels. Control of achievement of development targets is used to determine which areas are priorities. The TOPSIS method is a multi criteria  decision making method that has simple concepts and efficient computation and has the ability to measure the relative performance of decision alternatives in mathematical form. To make it easier to find priority areas, the method of Technique for Other Reference by Similarity to Ideal Solution is used. The purpose of this research is to get a decision-making model of development priority areas using criteria based on the number of places of worship, damaged roads, roads not yet built, water tunnels, street lighting and the place of residents' activities in the Tekad Village as the central village of Pulau Panggung sub-district whose territory has opened up many new settlement areas. Of the 10 alternatives tested in this study, an alternative V2 was obtained with the lowest value of 0.244569 as a lack of infrastructure in the area so that it was declared to be a priority development area in the Tekad Village.